Software‐guided Microfluidic Reaction Calorimeter Based on Thermoelectric Modules. Issue 5 (10th March 2021) - Frede, Timothy Aljoscha; Burke, Inga; Kockmann, Norbert
Abstract: A software‐guided, continuous reaction calorimeter based on thermoelectric modules for direct heat flux measurements is presented. Sensors and actuators of the calorimeter's setup are implemented within a lab automation system, which enables the automated calibration of the heat flux sensors and investigations of chemical reactions through sequential function charts. Functionality of the calibration is shown by heat transfer experiments. Additionally, the calorimeter's performance is demonstrated by good agreement of conducted neutralization experiments with literature data. Abstract : An automated calibration method was developed for isoperibolic operation mode of a microfluidic reaction calorimeter in continuous flow with commercially available glass plate microreactors. This presented method is validated by neutralization reaction experiments.